The role of spiritual intelligence in the effectiveness of crisis management A survey research for the opinions of a sample of medical personnel working in hospitals Designated to receive patients (COVID19) in the city of Sulaymaniyah/Iraq - Asad, Zahra; Rostam, Sarwat; Hama Saeed, Soran (Dirasat: Human and Social Sciences, 2022)
The aim of the research is to study the relationship of spiritual intelligence and its effect on the effectiveness of crisis management in some hospitals in the city of Sulaymaniyah,. a hypothetical model was created that clarifies the relationship between the dimensions of spiritual intelligence and the effectiveness of managing the crisis , and the research adopted the descriptive analytical approach and adopted a questionnaire form as a tool to collect and analyze data according to the (Thurston) decimal scale The questionnaire was submitted electronically to the research community, and (60) responses were obtained , and a set of conclusions were reached, including: The existence of a relationship and moral impact between the dimensions of spiritual intelligence and effectiveness Managing the crisis by removing it individually and collectively, providing high levels of spiritual intelligence among the medical cadres working in the research hospitals It contributed greatly to effective crisis management, and a set of recommendations was presented .